Factors influencing transfer of training at Wearnes Autohaus Sdn. Bhd. / Nuraidil Syahfiq Aididin - Aididin, Nuraidil Syahfiq (Faculty of Business and Management, 2019)
Transfer of training is important because it leads to improve employee performance in organization. This study identifies the factors influence transfer of training in Wearnes Autohaus Sdn. Bhd., Johor Bahru. The independent variable on this study are training design, individual characteristics and work environment. Meanwhile, the dependent variable is transfer of training. Data of this study were collected through the questionnaires that were distributed to the respondent. Then, data were analysed by using Statistical Procedure Social Science (SPSS). The sampling technique that used in this study is simple random sampling. Total of the questionnaire that has been distributed is 54 and only 52 questionnaires had been collected. The result of this study revealed that training design, individual characteristics and work environment has positive significance influence on transfer of training.